2007
DOI: 10.1089/vim.2006.0096
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Dysfunction by Hepatitis C Virus Core Protein Involves PD-1/PDL-1 Signaling

Abstract: Reports have shown that a negative T cell costimulatory pathway mediated by PD-1 (programmed death-1) and PDL-1 (programmed death ligand-1) is associated with T cell exhaustion and persistent viral infection. Persistent hepatitis C virus (HCV) infection in humans is also characterized by impaired T lymphocyte function, but the role of the PD-1 and PDL-1 pathway in HCV infection is unknown. Here we report that T cells isolated from chronically HCV-infected patients express significantly higher levels of PD-1 wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 37 publications
2
86
0
3
Order By: Relevance
“…For example, the HCV core protein induces PD-1 expression in T cells and monocytes (45,79). Lipopolysaccharide (LPS) and HIV-1 virions can induce PD-L1 expression in neutrophils (80).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the HCV core protein induces PD-1 expression in T cells and monocytes (45,79). Lipopolysaccharide (LPS) and HIV-1 virions can induce PD-L1 expression in neutrophils (80).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant C protein also has a number of inhibitory effects on TcR signaling, including impaired activation of the signaling molecules Lck, ZAP-70, Akt, ERK, and MEK, upregulation of T-cell expression of the negative regulator PD-1, and cell cycle arrest. These effects have been reported to be dependent upon the interaction of C protein with the complement receptor gC1qR (72,(166)(167)(168)(169), which may facilitate the entry of C protein into T cells (31). In support of the importance of C protein in vivo, transgenic mice with C protein expression targeted to T cells by the CD2 promoter showed markedly depressed IL-2 and gamma interferon production after anti-CD3 stimulation of splenocytes (141).…”
Section: (And Other Morbilliviruses)mentioning
confidence: 99%
“…It has been shown that interaction of the HCV C protein with cellular molecules impairs the host's immune response through mechanisms that result in the suppression of interleukin-12 synthesis in human macrophages (37), T cell dysfunction (38), and inhibition of T-lymphocyte activation and proliferation (25,39,40). In Friend leukemia cells treated with IFN, the induction and production of leukemia viruses are inhibited while induction of HB is slightly increased (33).…”
Section: Discussionmentioning
confidence: 99%